(untitled) - International center for Aquaculture (Alabama, 1991)
This report summarizes a more comprehensive economic evaluation of aquaculture as a foreign assistance development activity.
Keywords: Fishery management,Fish culture,Freshwater fishes,Quản lý nghề cá; Developing countries,Developing countries,Developing countries